2019
DOI: 10.3389/fnins.2019.01292
|View full text |Cite
|
Sign up to set email alerts
|

Mental Effort and Information-Processing Costs Are Inversely Related to Global Brain Free Energy During Visual Categorization

Abstract: Mental effort is a neurocognitive process that reflects the controlled expenditure of psychological information-processing resources during perception, cognition, and action. There is a practical need to operationalize and measure mental effort in order to minimize detrimental effects of mental fatigue on real-world human performance. Previous research has identified several neurocognitive indices of mental effort, but these indices are indirect measures that are also sensitive to experimental demands or gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…Further, researchers have found that making decisions with uncertainty requires more of our limited mental effort than judgments without uncertainty ( Sprenger and Dougherty, 2006 ). Researchers in psychology and cognitive science have established that mental effort involves the controlled use of our limited ability to process information at a given time ( Trujillo, 2019 ). As the number of uncertainties in a multiple hazard visualization increases, decision-makers will be forced to expend more of their limited mental effort until they reach their maximum.…”
Section: Multiple Hazard Uncertainty Communication Challenges and Paths Forwardmentioning
confidence: 99%
“…Further, researchers have found that making decisions with uncertainty requires more of our limited mental effort than judgments without uncertainty ( Sprenger and Dougherty, 2006 ). Researchers in psychology and cognitive science have established that mental effort involves the controlled use of our limited ability to process information at a given time ( Trujillo, 2019 ). As the number of uncertainties in a multiple hazard visualization increases, decision-makers will be forced to expend more of their limited mental effort until they reach their maximum.…”
Section: Multiple Hazard Uncertainty Communication Challenges and Paths Forwardmentioning
confidence: 99%
“…[27,98,99] A closely linked concept to CF is cognitive workload. Cognitive workload applies an ergonomic and human factors model (eg, elements of a job or task that create a feeling of mental work) to understand fatigue as it relates to sustained work performance [100][101][102][103][104]. The NASA-TLX is a commonly used measure of workload [105,106].…”
Section: Fatigue Assessmentmentioning
confidence: 99%
“…[27,98,99] A closely linked concept to CF is cognitive workload. Cognitive workload applies an ergonomic and human factors model (eg, elements of a job or task that create a feeling of mental work) to understand fatigue as it relates to sustained work performance [100][101][102][103][104]. The NASA-TLX is a commonly used measure of workload [105,106].…”
Section: Fatigue Assessmentmentioning
confidence: 99%